2020
DOI: 10.1016/j.neuron.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crux of Hair Cell Mechanotransduction Machinery

Abstract: Although 62 years have elapsed since the first report of hereditary deafness in a mouse strain, the molecular mechanism of hair cell mechanotransduction remains elusive. Three recent studies present crucial insights into the molecular crux of hair cell mechanotransduction machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Mechanosensitive channels can be made up of several subunits. For example, in hair cell, mechanoelectrical transduction channels consist of transmembrane channel-like 1 and 2 (TMC1/2), transmembrane inner ear (TMIE), transmembrane proteins lipoma HMGIC fusion partner-like 5 (TMHS/LHFPL5), and may be more [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanosensitive channels can be made up of several subunits. For example, in hair cell, mechanoelectrical transduction channels consist of transmembrane channel-like 1 and 2 (TMC1/2), transmembrane inner ear (TMIE), transmembrane proteins lipoma HMGIC fusion partner-like 5 (TMHS/LHFPL5), and may be more [24].…”
Section: Discussionmentioning
confidence: 99%
“…MeT channels open very quickly and the channel latencies are typically less than 20 ms [31,41,52]. To date, members of four classes of membrane proteins that are related to mechanotransduction are considered to be pore-forming subunits of MeT channels: TRP, DEG/ENaC, Piezo, and TMC [31,32,34,38,53,54]. mechanotransduction channels [21,38,40,52].…”
Section: A Novel Sodium-sensitive Channel In Mechanotransductionmentioning
confidence: 99%
“…The single-tether model is simple with an intracellular tether and membrane forces congregate to regulate the passage of ions across the channel (Chalfie, 2009). The gating mechanism of hair cell mechanotransduction might be very complex incorporating features of known tethering models and more (Al-Sheikh & Kang, 2020). For instance, ankyrin recently reported to tether the cytoskeleton and the TMC/CIB complex, conforms to the dual-tether model alongside the tip link proteins (PCDH15/CDH23) (Tang et al, 2020).…”
Section: Gating Mechanismmentioning
confidence: 99%
“…Whereas, another latest study about TMIE and PIP 2 (Phosphatidylinositol 4, 5-bisphosphate) revealed to promote membrane tension and mechanosensation (Cunningham et al, 2020). As such, the mammalian hair cell mechanotransduction machinery is still enigmatic even after 62 years since the first report of hereditary deafness in a mouse model (Al-Sheikh & Kang, 2020).…”
Section: Gating Mechanismmentioning
confidence: 99%
See 1 more Smart Citation